Recent Weed Control, Weed Management, and Integrated Weed Management - Harker, K. Neil; O'Donovan, John T (Weed technology, 2013)
Integrated weed management (IWM) can be defined as a holistic approach to weed management that integrates different methods of weed control to provide the crop with an advantage over weeds. It is practiced globally at varying levels of adoption from farm to farm. IWM has the potential to restrict weed populations to manageable levels, reduce the environmental impact of individual weed management practices, increase cropping system sustainability, and reduce selection pressure for weed resistance to herbicides. There is some debate as to whether simple herbicidal weed control programs have now shifted to more diverse IWM cropping systems. Given the rapid evolution and spread of herbicide-resistant weeds and their negative consequences, one might predict that IWM research would currently be a prominent activity among weed scientists. Here we examine the level of research activity dedicated to weed control techniques and the assemblage of IWM techniques in cropping systems as evidenced by scientific paper publications from 1995 to June 1, 2012. Authors from the United States have published more weed and IWM-related articles than authors from any other country. When IWM articles were weighted as a proportion of country population, arable land, or crop production, authors from Switzerland, the Netherlands, New Zealand, Australia, and Canada were most prominent. Considerable evidence exists that research on nonherbicidal weed management strategies as well as strategies that integrate other weed management systems with herbicide use has increased. However, articles published on chemical control still eclipse any other weed management method. The latter emphasis continues to retard the development of weed science as a balanced discipline. El manejo integrado de malezas (IWM) puede ser definido como un enfoque holístico del manejo de malezas que integra diferentes métodos de control para brindar al cultivo una ventaja sobre las malezas. Esto es practicado globalmente con niveles de adopción que varían de finca a finca. El IWM tiene el potencial de restringir las poblaciones de malezas a niveles manejables, reducir el impacto ambiental de prácticas individuales de manejo de malezas, incrementar la sostenibilidad de los sistemas de cultivos y reducir la presión de selección sobre la resistencia a herbicidas de las malezas. Existe cierto debate acerca de si programas de control de malezas basados simplemente en herbicidas, ahora se han convertido a sistemas de cultivos con IWM más diversos. Dada la rápida evolución y dispersión de malezas resistentes a herbicidas y sus consecuencias negativas, uno podría predecir que la investigación en IWM sería actualmente una actividad prominente entre científicos de malezas. Aquí examinamos el nivel de actividad investigativa dedicada a técnicas de control de malezas y al ensamblaje de técnicas de IWM en sistemas de cultivos, usando como evidencia la publicación de artículos científicos desde 1995 al 1 de Junio, 2012. Autores de los Estados Unidos han publicado más artículos relacionados a malezas y a IWM que autores de cualquier otro país. Cuando se ajustó el peso de los artículos de IWM como proporción de la población del país, tierras arables o producción de cultivos, autores de Suiza, Holanda, Nueva Zelanda, Australia y Canadá fueron los más prominentes. Existe considerable evidencia de que ha incrementado la investigación sobre estrategias no-herbicidas de manejo de malezas y también sobre las estrategias que integran otros sistemas de manejo de malezas con el uso de herbicidas. Sin embargo, los artículos publicados sobre control químico todavía eclipsan cualquier otro método de manejo de malezas. Este último énfasis continúa retrasando el desarrollo de la ciencia de malezas como una disciplina balanceada.